Use of temporary interventions to reclaim neglected urban spaces (Journal of Planner and Development, 2019)
The research deals with one of the urban problems facing cities, namely the existence of neglected urban spaces that need to be activated , These spaces give a negative image of the city, is not conducive to life and social interactions or the city has a one distinctive urban experience, leading to a reduction peoples’ confidence in revisiting of those areas, hinder the rest of the activities in that region . Because these spaces are of the basic components of the city and give it its identity through the elements and entities that constitute it , The idea of research emerged in the reclaiming of these spaces within contemporary urban trends and the activation of flexible , short-term and inovation for that purpose within the fabric of the city. The research problem : (The need to clarify the nature of urban physical interventions contributing to the activation of neglected urban space) For the purpose of solving the problem of research, a method is required consisting of several stages, first: to identify the types of temporary interventions adopted in the neglected spaces, second: selecting which contributed to the activation of space through a practical study on an elected sample (Khader Elias region)Keywords: reclaiming , temporary intervention, types of temporary interventions, objectives of temporary intervention